Basic thermodynamics - Guha, Evelyn ([S.l.] : Narosa Publishing House, 2000)
The book presents a clear and simple exposition of thermodynamic principles to enable beginners to penetrate its fundamental ideas buried under a haze of abstractness and to appreciate the logical development of thermodynamic reasoning. Since thermodynamics often proves conceptually difficult for the beginner, care has been taken to present a clear and simple but comprehensive account of its principles. Applications in various branches of physics (phase transitions, low temperature physics, thermal radiation, power and refrigeration cycles) have been treated in some detail. Worked examples and a set of problems accompany each chapter.
Keywords: thermodynamics